2015
DOI: 10.7759/cureus.268
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note – Lateral Approach to the Lumbar Spine for the Removal of Interbody Cages

Abstract: Revision surgery to address the migration or fracture of a lumbar interbody cage can be technically challenging. Scar tissue and fibrosis, among other anatomic barriers, can make removal of the cage a complicated procedure, potentially increasing postoperative pain as well as the probability of neurologic deficits. Use of the lateral surgical technique for removal of the cage can avoid these potential complications. In this case report, we describe the removal of interbody cages through a lateral approach in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…In the current study, we isolated and characterized 17 28,40,41 In the current study we reported the first isolation of M. lehmannii, N. neocaledoniensis, S. heliomycini, and A. crystalopoetis from clinical samples.…”
Section: Discussionmentioning
confidence: 88%
“…In the current study, we isolated and characterized 17 28,40,41 In the current study we reported the first isolation of M. lehmannii, N. neocaledoniensis, S. heliomycini, and A. crystalopoetis from clinical samples.…”
Section: Discussionmentioning
confidence: 88%
“…3 The characteristics of GBM include rapid invasive growth, diffused infiltration, strong angiogenesis, and extensive genomic instability. 4 At present, the primary therapeutic methods for patients with GBM include surgical resection, radiotherapy, and chemotherapy. 5 Despite tremendous progress in the techniques for GBM diagnosis and therapy, the clinical outcomes of patients with GBM remain dissatisfactory, and the median survival time is less than 20 months after diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its ease and minimally invasive direct access to the anterior lumbar spine, the technique increases safety by avoiding an area that has been affected by previous surgeries6). However, the lateral approach also has disadvantages associated with the approach pathway.…”
Section: Discussionmentioning
confidence: 99%